Organização da produção em uma montadora automobilística que opera em regime CKD: uma abordagem emitente-destinatário - Freitas, Larissa Diniz (2015)
In order to overcome the barriers to break into foreign markets and expand the presence of their business, some companies take hold of strategic partnerships. One of these production strategies is the Completely Knocked Down (CKD), which aims to attend nationalization requirements in recipient countries. Although they facilitate internationalization, supply chains CKD face constraints caused by the large distance between supplier and customer, making logistics operations less consistent and less flexible. The problem that motivated this thesis came from a logistics project demanded by a national CKD automaker experiencing problems with the lack of an efficient logic of occupation of its warehouses and the high level of handling of parts in the supplying process. The aim of this work is to present and discuss the operational logistics of CKD production system in the automotive industry from a case study, trying to understand what conditions a CKD chain of supplies produce on the production operations of an assembly plant and how to operationalize the CKD system before the implications of their conditions impose the production system. The research method used was the single case study, using research from several sources of evidence. The transactions of materials and information between the supplier and CKD national carmaker were investigated, and internal logistics processes the automaker until the release of vehicles for distribution in dealerships. The case study revealed that there are different logics that influence the internal logistics operations to the assembler. The issuer's logic, that is, the CKD supplier, influences the receiving processes and blocking parts of the automaker; recipient's logic, or rather the automaker itself, influences the supply of assembly lines; and distribution of logic, led by the market and holding company that operates the automaker, influences the production and distribution of the vehicles produced. Solutions have been proposed to mitigate the effect of these constraints in order to make the logistic process of the company more efficient and effective by redefining the supply of parts approach and the redefinition of the shipping configuration of CKD materials.